LINE WEBTOON SEBAGAI INDUSTRI KOMIK DIGITAL - Lestari, Annisa Fitriana; Irwansyah, Irwansyah (SOURCE : Jurnal Ilmu Komunikasi, 2020)
Because of internet and smartphones, various industries and their products have changed. Comics as one form of the reading industry also experienced this impact. Conventional comics are changing into digital comics, which can be read via cellphones. One of the digital comic services is LINE Webtoon, which has successfully become a popular comic application in various countries, including Indonesia. The purpose of this study is to provide an overview, deepen and develop the concept of Webtoon, especially LINE Webtoon. This research using qualitative descriptive as method. The results showed that the Webtoon was developed from a conventional form of comics in South Korea called manhwa. Manhwa change into digital because the decline of conventional comic market and technological advancements that developed in South Korea. As an industry, LINE Webtoon expanded its business with presenting paid content, creating advertisements, looking for talented comics, and adapting across media to popular Webtoon works.